“PENGARUH KONSUMSI MINUMAN MENGKUDU (Morinda citrifolia) TERHADAP TEKANAN DARAH PADA USIA LANJUT PENDERITA HIPERTENSI - Intan Hanifah Mutmainnah (FKU 16 UMY 185, 2016)
Hypertension is a disease that can cause death without any prior signs or symptoms to the sufferer. Hypertension is often called the silent killer. Hypertension is also a major risk factor in stroke, heart failure, coronary artery disease and kidney failure. As for traditional therapy that can control hypertension is the noni fruit (Morinda citrifolia) containing scopoletin because it can dilate blood vessels. The aim of this study is to assess the effect of beverage consumption of noni (Morinda citrifolia) on blood pressure of hypertensive patients and provide the benefits of alternative therapies. An experimental study conducted in 32 elderly hypertensive patients, divided 2 groups with research design pre and post test blood pressure values, then given therapy drinks noni (Morinda citrifolia) with the dose of 500 mg and 1000 mg. The results of the study systolic diastolic blood pressure values obtained 11 votes of noni regularly consume beverages with a dose of 500 mg and 14 people at a dose of 1000 mg. Analysis of Paired T-Test systolic blood pressure values doses of 500 mg and 1000 mg produces p = 0.000 means that there are significant effect of consuming noni beverage towards systolic blood pressure. The analysis result of Paired T-Test values diastolic blood pressure of a dose of 500 mg produces p = 0.004 and p = 0.093 at a dose of 1000 mg means that there are significant effect of consuming noni beverage towards diastolic blood pressure is 500 mg and no effect of consuming noni drinks to diastolic blood pressure with the dose of 1000 mg. Therefore the consumption of noni drinks dose 500 mg has a greater influence than dose 1000 mg. Keyword : Hypertension, Morinda citrifolia, scopoletin, dose, blood pressure